Penerapan pemantauan sistem manajemaen keselamatan dan kesehatan kerja di PT. Anugrah Karya Pasti Parang Magetan - Rachmat Nugroho; Pipid Ari Wibowo; Karina Nur Ramadhanintyas (Poltekkes Kemenkes Aceh, 2024)
Background: Occupational safety and health management system or abbreviated SMK3 is a management concept aimed at companies to protect workers to avoid work accidents and prevent work-related illnesses in order to create an effective, safe and productive workplace. Based on the preliminary survey, information is needed that there has not been an occupational safety and health management system (SMK3) program since 2016.Objectives: The purpose of this study was to determine the implementation of monitoring of the occupational health and safety management system K3 at PT. Anugrah Karya Pasti Parang Magetan.Methods: This research is a qualitative research using Qualitative research with the type of rapid assessment procedures (RAP) on the description of K3 performance monitoring and evaluation. There were 5 informants in this study, namely 2 excavator operators, 1 helper, 1 foreman and 1 company leader. Data collection was carried out by interviewing workers and the results of field observations.Results: The results of this study indicate the monitoring and evaluation of K3 performance at PT. Anugrah Karya Pasti is not in accordance with Government Regulation Number 50 of 2012 concerning SMK3 and does not have an K3 expert but has carried out inspections before work begins and during breaks.Conclusion: The conclusion of this study has not implemented SMK3 at PT. Definite Work Award. Suggestions for PT. Anugrah Karya Pasti immediately implements SMK3 in accordance with the applicable laws and regulations.KeywordsK3 performance evaluation, K3 monitoring, SMK3